2003
DOI: 10.2323/jgam.49.235
|View full text |Cite
|
Sign up to set email alerts
|

Effect of support materials on antibiotic MSW2000 production by immobilized Streptomyces violatus

Abstract: The production of an antibiotic by free and immobilized cells of Streptomyces violatus through entrapment or adsorption on different materials was investigated. S. violatus entrapped in Ca-alginate beads gave low antibiotic activity compared to the free cell or adsorbed cell, while the adsorption of S. violatus on sponge cubes yielded the highest antibiotic concentration after 4 days of incubation in static cultures. A starch concentration of 10 g/L was optimum for the production of the antibiotic by adsorbed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 30 publications
1
13
0
Order By: Relevance
“…Thus, standing condition is more suitable for antibiotic production. These results were in agreement with El-Naggar et al [23] who reported the highest production of antimicrobial substances by S. violates occurred after four days of incubation period under static conditions. Miyoshi et al [24] who observed an increase in agitation led to the loss of antibiotic production, but a high level of production obtained at static condition.…”
Section: Incubation Period and Agitationsupporting
confidence: 93%
See 2 more Smart Citations
“…Thus, standing condition is more suitable for antibiotic production. These results were in agreement with El-Naggar et al [23] who reported the highest production of antimicrobial substances by S. violates occurred after four days of incubation period under static conditions. Miyoshi et al [24] who observed an increase in agitation led to the loss of antibiotic production, but a high level of production obtained at static condition.…”
Section: Incubation Period and Agitationsupporting
confidence: 93%
“…The effect of pH is ionizing the nutrients to facilitate uptake by microorganisms and to stimulate production pathways of antibiotics. Many researchers documented that the pH value of antibiotic production medium has different influences to guide the production toward positive or negative directions depending on the microorganism categories; in other words, any microorganism such as Streptomyces aburaviensis, Streptomyces violates, and Pseudonocardia needs optimal pH for highest antibiotic production, which had the maximum antibiotic yield at pH of 9, 7.5, and 7, respectively [5,6,[17][18][19][20][21][22][23].…”
Section: Initial Ph Of the Media And Incubation Temperaturementioning
confidence: 99%
See 1 more Smart Citation
“…Optimal production has been achieved by cultivating organisms in media containing slowly utilized nutrient sources [22] [23]. Starch has been found to be the best carbon source for antibiotic production by several researchers [24] [25].…”
Section: Effect Of Carbon Sources On Growth and Bioactive Metabolite mentioning
confidence: 99%
“…The cultural factor optimization plays a remarkable role in the productivity and economics of the essential process [13][14][15][16][17][18][19]. Hence, our study was aimed to the isolation of Streptomyces sp.…”
Section: Introductionmentioning
confidence: 99%